A Systematic Literature Review the Use of Quizizz on EFL Students’ Vocabulary Mastery: A Shift from Pandemic to Post-Pandemic - Rizkiawati, Hernandini; Santosa, Made Hery; Indrayani, Luh (English Education Department STKIP Agama Hindu Singaraja, 2024)
The impact of the Covid-19 pandemic has highlighted the importance of gamification in education, with Quizizz emerging as a popular tool for interaction between teachers and students. This systematic review focuses on previous research examining the effects of Quizizz on vocabulary skills, particularly among English as a Foreign Language (EFL) learners. Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the study accessed ten journal articles published between 2019 and 2024 via Google Scholar and Crossref. Through rigorous review processes, including inclusion and exclusion criteria, this review investigates how Quizizz is utilized in educational settings to enhance student vocabulary skills. The findings underscore Quizizz's potential to offer engaging features that facilitate vocabulary learning and improvement among students The practical implications of this study suggest that EFL teachers should consider integrating Quizizz into their classrooms. Quizizz can effectively complement traditional teaching methods or be utilized independently for vocabulary practice. Future research should explore the long-term effects of using Quizizz on vocabulary retention, its applicability across different proficiency levels, and its impact on students' motivation for vocabulary acquisition.